Peningkatan Kreativitas Siswa Dengan Menggunakan Langkah-Langkah Polya Dalam Materi Sistem Persamaan Dan Pertidaksamaan Linear Dua Variabel Dan Sistem Persamaan Linear Tiga Variabel (PTK Pada Siswa Kelas X MIA 3 SMA Negeri 1 Kradenan Tahun 2015/2016) - Noor Fitriana, Nisa (2016)
The purpose of this research is to improve creativity of students by using Polya Strategy.This research is a classroomaction research consisting of two cycles. The research subjects were students of class X MIA 3 SMAN 1 Kradenan The technique of data collection is observation, field notes, test, and documentation.The technique of data analysis using flow method is the process of data reduction, data presentation, and Verification. The results of this research showed that an increase in creativity skills of student, it can be seen from: 1) the ability of students to find the problem and the idea/ideas, before the action 27.7%, after the action increased to 86.1%, 2) the ability of students in finding a solution matter before action 33.3%, after the action to 80.5%, 3) the ability to conclude before action 22.2%, after the action increased to 83.3%, 4The research concluded that the Steps of polya can improve creativity of students learning class X MIA 3 SMA Negeri 1 Kradenan.